Modeling and Position Control of a Marine Vehicle with Omnidirectional Configuration (Contemporary Mathematics, 2025)
One of the main means of monitoring aquatic bodies are buoys, most of which are fixed, so they are not flexible enough to perform tasks such as: cleaning; rescue; exploration and surveillance. Therefore, this work is dedicated to the mathematical modeling and design of control schemes for a compact buoy with omnidirectional configuration to move between two desired points in a given time; this configuration allows the buoy to converge accurately and quickly to desired positions and routes, however, disturbances due to waves must be considered, which directly affect the movement of the buoy. These disturbances can be compensated by a robust motion controller. Thus, the dynamic model of the buoy is obtained and two control schemes are developed: Proportional-Derivative-Plus controller and Backstepping controller. These controllers base their design on a Lyapunov candidate function, which guarantees the stability of the system; however, they depend on the parameters of the dynamic model. Therefore, the dynamic buoy model is obtained considering environmental disturbances such as wind and waves. The mathematical model and the control algorithms are simulated and compared in MATLAB/Simulink. The comparison is made considering the presence of environmental disturbances from waves and wind. In addition, the evaluation was carried out using performance indicators such as variation in control efforts and those based on error: integral error, absolute integral error, and mean square error.
Keywords: backstepping controller; marine systems; omnidirectional configuration; PD controller; vehicle dynamics